Figs 46–53 in Coccolithophorids in Polar Waters: Pappomonas spp. Revisited ... - Thomsen, Helge A.; Østergaard, Jette B. (Zenodo, 2014)
Figs 46–53. Balaniger virgulosa HET from the Arctic (West Greenland / Figs 46–47, 49; NEW / Fig. 50; Spitsbergen / Figs 51–53; Bergen, Norway / Fig. 48); TEM (Figs 46–47, 49–50) and SEM (Figs 48, 51–53) whole mounts. 46 – complete cell with reduced central appendages on some coccoliths at the posterior cell end; 47 – detail of cirtcumflagellar coccolith central processes showing the shaft and the tuft of four elongate elements that terminate the structure; 48 – detail of specimen from western Norway showing central area features of a circumflagellar coccolith; 49 – detail of body coccoliths showing the rim and central area calcification; the arrows point to areas where the calcification is particularly evident; 50 – complete cell with flagella and a curled up haptonema; 51 – whole cell which shows the irregular arrangement of densely packed body coccoliths; 52 – combination cell comprising Pappomonas virgulosa and Balaniger balticus; interspersed between the widely separated body coccoliths is a layer of ... : Published as part of Thomsen, Helge A. & Østergaard, Jette B., 2014, Coccolithophorids in Polar Waters: Pappomonas spp. Revisited, pp. 235-256 in Acta Protozoologica 53 (3) on page 252, DOI: 10.4467/16890027AP.14.022.1997, http://zenodo.org/record/12638350 ...